Elucidating the structure and functions of Resolvin D6 isomers on nerve regeneration with a distinctive trigeminal transcriptome. Issue 8 (10th July 2021) - Pham, Thang L.; Kakazu, Azucena H.; He, Jiucheng; Nshimiyimana, Robert; Petasis, Nicos A.; Jun, Bokkyoo; Bazan, Nicolas G.; Bazan, Haydee E. P.
Abstract: Innervation sustains cornea integrity. Pigment epithelium‐derived factor (PEDF) plus docosahexaenoic acid (DHA) regenerated damaged nerves by stimulating the synthesis of a new stereoisomer of Resolvin D6 (RvD6si). Here, we resolved the structure of this lipid isolated from mouse tears after injured corneas were treated with PEDF + DHA. RvD6si synthesis was inhibited by fluvoxamine, a cytochrome P450 inhibitor, but not by 15‐ or 5‐LOX inhibitors, suggesting that the 4‐ and 17‐hydroxy of DHA have an R R ‐ or S R ‐configuration. The two compounds were chemically synthesized. Using chiral phase HPLC, four peaks of RvD6si1‐4 from tears were resolved. The R R ‐RvD6 standard eluted as a single peak with RvD61 while pure S R ‐RvD6 eluted with RvD63 . The addition of these pure mediators prompted a trigeminal ganglion transcriptome response in injured corneas and showed that R R ‐RvD6 was the more potent, increasing cornea sensitivity and nerve regeneration. R R ‐RvD6 stimulates Rictor and hepatocyte growth factor ( hgf ) genes specifically as upstream regulators and a gene network involved in axon growth and suppression of neuropathic pain, indicating a novel function of this lipid mediator to maintain cornea integrity and homeostasis after injury.